Disabilities and vulnerabilities - Jehan, Talat; Termizi, Mazbah; Abdullah, Nurhidayah (2022)
Persons with special needs and disabilities are more likely to experience adverse socioeconomic outcomes such as less education, poorer health outcomes, lower levels of employment, and higher poverty rates. Disable or differently-able people are considered to be the most vulnerable or even in majority of countries as one of the neglected and marginalized segment of our society who are mostly at risk when there is any kind of emergency, disaster, pandemic (such as COVID-19) because of their vulnerability and being at risk. The purpose of the study is to refer and highlight the deprivations of people with disabilities (PWDs) have to face on continuous basis. Although conventions like Convention on the Rights of Persons with Disabilities (CRPD) focuses on the change of attitudes and approaches to persons with disabilities but still there are different disabilities who still do not have equal human rights and fundamental freedoms in the 21st century. We still overlook the needs of people with disabilities during such difficult situations to a large extent. As it is evident from our previous experience since the outbreak of this COVID-19, such pandemics have multidisciplinary problems and issues, especially from a disability perspective, because their effects are partly medical and partly socioeconomic and psychological, and when the end beneficiary or victim is disable then the repercussions are harmful and long-lasting, and such victims are traumatized and psychologically more impacted than the normal humans like us. In terms of responsibility state is the first actor who is responsible to act immediate and take an immediate and necessary measures to ensure the protection and safety of persons with disabilities in situations of risk, including situations of armed conflict, humanitarian emergencies and 2 the occurrence of natural disasters. Furthermore, PWDs could be multiple challenges when on one hand they are physical/mentally challenged or on the other hand they are poor, uneducated, they sick and frail, and having disadvantages in society, and due to these factors they are at much greater risk when a pandemic arrives. Moreover, such pandemics are indiscriminatory in a sense that almost entire population globally was impacted equally, but again when it comes to cater the special needs of disabled people, we have stay one step ahead so they can feel equally valued and respected. Also, from another angel elderly people are also considered because of their age and dependency of others, as not all elderly people are disabled, but disability becomes more likely with the bodily deteriorations that age can cause. People with disabilities who live alone may suffer isolation and feel anxiety continuously. The elderly may have lost friends and partners, and they may suffer long-term deterioration in their health, leading to disability as a result thereof. Additionally, disabled people have many of the same fears and undergo the same stresses that are experienced by nondisabled people, but they may be dealing with the prospect of more serious consequences. In terms of methodology, content analysis as a qualitative tool was used to analyze different content and its features, such as international conventions and frameworks, evidence based info-graphics, Sustainable Development Goals PiCCWED15, 24 September 2022 Page 25 (SDGs) and charters. With regard to its significance, this research also focuses and considers recent observations and studies suggested and endorsed that that many people with disabilities are good at adapting to adversity and are well aware of the sources of help or emotional support. They may use religion, humour or acceptance to help them cope with such hardships. On the negative side, they may in some cases resort to denial, which enables them to escape from the harsh reality of pandemic restrictions. Other maladaptive coping mechanisms involve substance abuse, detachment, behavioral disengagement, selfblame, guilt and venting. Keywords: PWDs, disability, pandemic, emergency, psychology, anxiety